G464 Polypharmacy in paediatric palliative care. (May 2019) - Mtunzi, NJM; Baba, M
Abstract : Background: Children under Paediatric palliative care (PPC) often have complex life-limiting conditions (LLC). Good symptom control is a cornerstone of treatment. Managing symptoms in children with complex LLCs often requires multiple medications on top of their disease-modifying medications, increasing the risks associated with polypharmacy. The relative paucity of evidence in this patient group may mean that in order to adequately manage some children's symptoms, doses outside the paediatric British National Formulary (BNFC) or Association of Paediatric Palliative Medicine (APPM) recommendations are sometimes used under specialist guidance, which may also contribute to the risks. Aims: To assess the extent of polypharmacy in children with LLCs. To identify the common drug-groups and medications prescribed for children with LLCs. To assess whether the drug doses prescribed for children with LLCs are higher than those indicated in the BNFC/APPM. Design: A retrospective drug chart review of 21 randomly selected children accessing children's hospice service was carried out. The data collected included; age, weight, drug, dose, frequency and route of administration. The drugs were grouped by type and doses were compared against BNFC/APPM formulary recommendations. The medication section of the care acuity review scoring (CARS) system in place at the hospice was used to assess the care burden of polypharmacy. Results: The mean number of medications used per child was 10 (range 3–23). 90% (n=19) of children scored ≥3 out of 4 in the CARS (table 1 ). The 6 most commonly used drugs were anti-epileptics (27%), analgesics (16%), laxatives (8%), anti-reflux (6%), muscle relaxants (6%) and anti-cholinergics (5%). 52% (n=11) of children were on at least one medication above the BNFC/APPM formulary recommended dose. Anti-epileptics and muscle relaxants doses were most frequently above recommendations and lorazepam had the highest average dose above the recommended dose. Conclusion: The study confirmed that polypharmacy in children accessing PPC is common and many are often on high doses, predisposing them to potential adverse effects. Conscientious review and careful rationalisation of prescribed medication coupled with a sound understanding of pharmacology are key to minimising the risks associated with polypharmacy.